(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Game-Based Learning is an innovative educational approach that leverages the engaging nature of games to enhance the professional skills of future engineers. By incorporating interactive simulations, challenges, and problem-solving scenarios into the learning process, GBL promotes active participation, critical thinking, and collaboration among students. This method bridges theoretical knowledge and practical application, preparing engineering students to face real-world challenges with creativity and confidence. This article explores the benefits of Game-Based Learning in engineering education and its role in developing essential professional competencies.